Comparative chromium adsorptive capacity of different low-cost materials using fixed bed column - Asma Shakeel; Inayat Mustafa Khan; Faheem Jeelani; Mukhtar Iderawumi Abdulraheem; Salma Imam Sulaiman; Mohmad Auyoub Bhat; Javid Ahmad Bhat; Tahir Sheikh; Rakshanda Anayat; Syed Andleeba Jan; Mehnaz Shakeel; Mohd. Tariq; et al. (Scientific Reports)
Abstract The accessibility of pure water is crucial for various human activities and is increasingly in demand due to the growing global population. Among the water-polluting substances, heavy metals are considered significant environmental threats regardless of the low concentrations, owing to their non-biodegradable, highly persistent and toxic features. Adsorption stands as a proficient method for the remediation of heavy metals in debt of its flexibility, reversibility, ability to produce high-quality treated water, and the potential to regenerate the adsorbent. Adsorption can be achieved using inorganic and organic adsorbents, using batch adsorption technique as well as the fixed-bed column approach. The current investigation entailing a continuous adsorption approach in a fixed-bed column was accomplished to appraise the Chromium [Cr(VI)] adsorption efficiency of three different adsorbent materials (Activated charcoal, Sawdust, and Rice husk). The study also sought to understand the impact of various operational parameters (flow rate, bed height and inflow metal concentration) on Cr (VI) adsorption by breakthrough curve analysis for optimizing the different column parameters required for a given heavy metal adsorption on a particular adsorbent. Activated charcoal used in the columns adsorbed elevated concentrations of Cr (VI) from chromium-spiked water. The proficiency of the employed adsorbents concerning the removal of Cr (VI) was in the order as follows: Activated charcoal > Rice husk > Sawdust. Analysis of the breakthrough curves revealed that lower inflow metal concentration, reduced inflow rate, and greater bed height of the material resulted in longer breakthrough times, indicating the ability to treat larger volumes of water before saturation. The breakthrough time for adsorption of Cr (VI) on sawdust ranged from 5.93 min to 11.85 min, while for rice husk and activated charcoal, it ranged from 6.13 min to 12.04 min and 11.02–21.06 min, respectively, under varying operational parameters. The optimal operational parameters aimed at maximum Cr (VI) removal from an aqueous solution containing 30 mg L-1 chromium are to maintain a bed depth of 30 cm with a solution flow rate of 30 ml min-1. The per cent removal of the chromium onto sawdust, rice husk, and activated carbon varied from 31.19 to 52.96%, 31.07–56.56%, and 37.71–66.32%, respectively, under varying operational parameters. Although Activated charcoal adsorbs higher Cr (VI) than the other two adsorbents, lower cost and easy availability of Sawdust and Rice husk can be recommended for the adsorption of Cr (VI) under the specified operational parameters in this column study. Furthermore, the study found that the derived R2 = 0.9476 demonstrated that the Yoon-Nelson model best described the Cr (VI) adsorption following the fixed-bed column system.